Developing Business Intelligence Dashboard for Sales KPI Monitoring in Advertising Agency: A Human-Centered Design Approach - Ince Ahmad Zarqan; Dimas Yudistira Nugraha; Ganda Tua Sitompul; Adli Abdillah Nababan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Digital advertising agencies in South Jakarta face significant challenges in monitoring sales performance due to data fragmentation across multiple platforms such as CRM, spreadsheets, and digital advertising tools. Conventional manual reporting processes lead to data latency, high error rates, and delayed strategic decision-making. This study aims to develop a Business Intelligence (BI) dashboard to monitor Sales Key Performance Indicators (KPIs) in real-time, utilizing a Human-Centered Design (HCD) approach to ensure high usability and adoption. The research methodology follows the ISO 9241-210 standard for HCD, encompassing four iterative phases: understanding the context of use, specifying user requirements, producing design solutions, and evaluating designs. The system was developed using Google Looker Studio with a data warehouse architecture integrating Google BigQuery. Testing was conducted involving 15 internal stakeholders using the System Usability Scale (SUS) and User Experience Questionnaire (UEQ). The results demonstrated a SUS score of 82.5 (Excellent) and positive benchmarks in efficiency and perspicuity metrics. The implementation of the dashboard reduced reporting time by 60% and improved data accessibility for executive decision-making. This study contributes to the literature by demonstrating how HCD principles can bridge the gap between technical BI capabilities and end-user cognitive needs in the creative industry context.